1. Limited time only! Sign up for a free 30min personal tutor trial with Chegg Tutors
    Dismiss Notice
Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Homework Help: Vec Calc - tangent to path

  1. Jan 19, 2006 #1
    The Problem: No clue how to begin the following. The textbook isn't too clear.

    Let [itex]f: \mathbb{R}^2 \rightarrow \mathbb{R}^2 ; (x,y) \rightarrow (e^{x+y}, e^{x-y})[/itex] Let c(t) be a path with c(0)=(0,0) and c'(0)=(1,1). What is the tangent vector to the image of c(t) under f at t=0?

    Any help at all would be much appreciated.
  2. jcsd
  3. Jan 19, 2006 #2


    User Avatar
    Homework Helper

    Let [tex] \vec{c}(t) = \left< x(t), y(t)\right> [/tex]

    then the image of c(t) under f is

    [tex] f( \vec{c}(t) ) = f(x(t), y(t)) = \left( e^{x(t)+y(t)},e^{x(t)-y(t)}\right)[/tex]

    The tangent vector is

    [tex] \frac{d}{dt} f( \vec{c}(t) ) =\frac{d}{dt} f(x(t), y(t)) = \frac{d}{dt}\left( e^{x(t)+y(t)},e^{x(t)-y(t)}\right) = \left( \frac{d}{dt} e^{x(t)+y(t)}, \frac{d}{dt} e^{x(t)-y(t)}\right) [/tex]
    [tex]= \left( e^{x(t)+y(t)}\left( x^{\prime}(t)+y^{\prime}(t)\right) , e^{x(t)-y(t)}\left( x^{\prime}(t)-y^{\prime}(t)\right) \right)[/tex]

    evalute at t=0 to get

    [tex]\left( e^{x(0)+y(0)}\left( x^{\prime}(0)+y^{\prime}(0)\right) , e^{x(0)-y(0)}\left( x^{\prime}(0)-y^{\prime}(0)\right) \right)[/tex]

    recall that c(0)=(0,0) and c'(0)=(1,1) and hence x(0)=0, y(0)=0, x'(0)=1, and y'(0)=1 so that

    [tex]\left( e^{x(0)+y(0)}\left( x^{\prime}(0)+y^{\prime}(0)\right) , e^{x(0)-y(0)}\left( x^{\prime}(0)-y^{\prime}(0)\right) \right) = \left( e^{0+0}\left( 1+1\right) , e^{0-0}\left( 1-1\right) \right) = \left( 2 , 0\right)[/tex]

    is the tangent vector to the image of c(t) under f at t=0.

    Though I'm not sure... is f a vector valued function of vectors?
    Last edited: Jan 19, 2006
  4. Jan 19, 2006 #3


    User Avatar
    Science Advisor

    Yes, that's exactly what [itex]f: \mathbb{R}^2 \rightarrow \mathbb{R}^2 ; (x,y) \rightarrow (e^{x+y}, e^{x-y})[/itex] means.

    And your solution is completely correct. It's really an exercise in using the chain rule.
  5. Jan 19, 2006 #4


    User Avatar
    Homework Helper

    Thanx Ivy.
Share this great discussion with others via Reddit, Google+, Twitter, or Facebook